Hybrid Plasmids Encoding Antimicrobial Resistance and Virulence Traits Among Hypervirulent Klebsiella pneumoniae ST2096 in India - Shankar, Chaitra; Vasudevan, Karthick; Jacob, Jobin John; Baker, Stephen; Isaac, Barney J.; Neeravi, Ayyan Raj; Sethuvel, Dhiviya Prabaa Muthuirulandi; George, Biju; Veeraraghavan, Balaji (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Hypervirulent variants of Klebsiella pneumoniae (HvKp) were typically associated with a broadly antimicrobial susceptible clone of sequence type (ST) 23 at the time of its emergence. Concerningly, HvKp is now also emerging within multidrug-resistant (MDR) clones, including ST11, ST15 and ST147. The MDR-hvKp either carry both the virulence and resistance plasmids or carry a large hybrid plasmid coding for both virulence and resistance determinants. Here, we aimed to genetically characterise a collection of MDR HvKp ST2096 isolates harbouring mosaic and hybrid plasmids carrying both antimicrobial resistance (AMR) and virulence genes. Methods: Nine K. pneumoniae ST2096 isolated over one year from the blood sample of hospitalised patients in southern India that were MDR and suspected to be HvKp were selected. All nine isolates were subjected to short-read whole-genome sequencing; a subset (n=4) were additionally subjected to long-read sequencing to obtain complete genomes for characterisation. Mucoviscosity assay was also performed for phenotypic assessment. Results: Among the nine isolates, seven were carbapenem-resistant, two of which carried blaNDM-5 on an IncFII plasmid, five carried blaOXA-232 on a ColKP3 plasmid. The organisms were confirmed as HvKp, with characteristic virulence genes (rmpA2, iutA and iucABCD) carried on a large (~320 Kbp) IncFIB-IncHI1B co-integrate. This hybrid plasmid also carried the aadA2, armA, blaOXA-1, msrE, mphE, sul1 and dfrA14 AMR genes in addition to the heavy metal resistance genes. The hybrid plasmid showed about 60% similarity to the IncHI1B virulence plasmid of K. pneumoniae SGH10 and ~70% sequence identity with the first identified IncHI1B pNDM-MAR plasmid. Notably, the hybrid plasmid carried its type IV-A3 CRISPR-cas system which harboured spacer regions against traL of IncF plasmids, thereby preventing their acquisition. Conclusion: The convergence of virulence and AMR is clinically concerning in K. pneumoniae. Our data highlight the role of hybrid plasmids carrying both AMR and virulence genes in K. pneumoniae ST2096, suggesting that MDR-HvKp is not confined to selected clones; we highlight the continued emergence of such genotypes across the species. The convergence is occurring globally amidst several clones and is of great concern to public health.